New Technology for Inclusive and Sustainable Growth Technological Support, Standards and Commercial Turnover - Inshakova, Agnessa O.; Inshakova, Elena I.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents body of knowledge on the economic, social and environmental impacts of the new Industry 4.0 technology use in view of regulating the related risks to ensure inclusive and sustainable growth in the Post-Soviet and selected developing countries while transition to a new technological order. The book brings together collected empirical evidence and pilot innovative research projects run by the author team that illustrate functional abilities, application potential and challenges of Industry 4.0 key enabling technologies (e.g., artificial intelligence, neural networks, blockchain, nanotechnology, etc.) and provides useful applied recommendations on managing the risks of their use in order to achieve economic growth fairly across society in the developed and developing countries. It presents suggestions to improve national legislation and existing economic regulations, which would also ensure boosting scientific research and training highly qualified personnel in computer, economic, administrative, legal and social sciences at the advanced universities and research institutions in the Post-Soviet area.
Constitutional Reform 2020 in Russia: Enhancing the Sovereignty and Independence of the State -- Elaboration of a Model for Sustainable Development in Organizations through Digital Integration of Management Systems Standards -- The Fourth Industrial Revolution and the State -- Transformation of Law and Legislation in the Context of Digitalization: Intellectual Property Protection -- On the Problem of Legal Regulation of Technologies with Elements of Artificial Intelligence -- Criminal Procedure Aspects of Fight against Economic Extremism among Young People -- Investing in Utilitarian Digital Rights as a Legal Mechanism for Improving the Welfare of the Population and a Factor of Inclusive Growth -- Protecting the Rights of Indigenous Peoples as an Essential Element of Inclusive Economic Growth -- Creative Industries in the Context of the Global Digitalization of Copyright -- Some Issues of Proof in Insurance Disputes in the Conditions of Digital Transformation of Law in Russia -- Legal Personality of Credit Institutions in the Civil Legislation of the Republic of Tajikistan.
Keywords: Industrial Management; Artificial intelligence; Blockchains (Databases).; Industrial Management; Artificial Intelligence; Blockchain; Artificial intelligence; Blockchains (Databases); Industry 4.0.; Technological innovations